THE IMPACT OF THE DIGITAL ECONOMY ON THE LABOR MARKET AND NEW PROFESSIONS (Marketing Journal, 2025)
This article provides a comprehensive analysis of the impact of the digital economy on the labor market. It examines the processes of job displacement and the emergence of new professions driven by artificial intelligence, automation, and the platform econ omy. Drawing on global statistical data and forecasts, the study 241 highlights worldwide trends and demonstrates the effects of digital transformation on Uzbekistanʼs labor market. Special attention is given to emerging roles such as AI specialists, data analysts, cybersecurity engineers, digital product managers, and othe r modern occupations. The article also presents recommendations for workforce reskilling and the development of future -oriented skills. The findings are practically relevant for public policy, the education system, and employers, contributing to sustainabl e employment in the era of the digital economy.
Keywords: digital economy; labor market; artificial intelligence; automation; platform economy; new occupations; reskilling; Uzbekistan